Civic participation and current educational reform in the sultanate of Oman - Al kharusi, Badar (Curtin University, 2011)
The main purpose of this exploratory study was to examine the Basic Education system in relation to students’ civic participation in the Sultanate of Oman. The research explores the role of formal curriculum, classroom climate, and co-curriculum activities in developing students’ civic participation. The study also examines students’ disposition towards civic participation and the influence of some demographic factors in the development of students’ civic participation. The data were collected from four schools implementing Basic Education system introduced in Oman in 1998. Using case study methodology, three instruments were used for data collection: semi-structured interviews with principals and teachers, focus groups with students and classroom observation in Grade 10 classes.The results suggest that the new formal curriculum aims and the suggested content creates further spaces in the Basic Education schools to support learners’ civic knowledge and commitment towards participation in public life. The findings also show that the investigated schools do experience some challenges in relation to successfully implementing the new formal curriculum. The findings related to classroom climate identify some positive practices that might develop civic participation in the students along the aspirations of the Basic Education policies. However, the data points out that various challenges remain before classes become more collaborative in their processes and more open to issues and concerns in the wider society. The findings also investigated a set of co-curricular activities as important spaces to develop participatory citizens. Nevertheless, the findings also show that various difficulties remain before the implemented co-curricular activities achieve their expectations as contributors to civic participation development. Finally, the findings show that students in general have a favourable disposition towards community participation. Female students were more knowledgeable about civic issues and were less interested in political participation than were male students. Socioeconomic background and school location were important factors in students’ access and participation in meaningful and varied civic learning opportunities.